Growth and Survival of Larvae (Trochus niloticus) as a Function of Light Density - Latama, Gunarto (Jurnal Moluska Indonesia, 2024)
Light is an important factor controlling the activity of the nocturnal snail Trochus niloticus. The importance of light for the survival and growth of the larvae was studied in aquaria exposed to the sunlight and compared to similar groups shaded by black nylon net. A higher number of larvae metamorphosed in the aquarium exposed to sunlight, but the average survival rate was highest in shaded aquaria. Survival increased significantly as a function of increasing degree of shading. A survival of 93.03 ± 2.86 % after 49 days was achieved after proper shading, thereby eliminating the major problem ofhigh mortality of T. niloticus in aquaculture. No significant difference was observed between light intensity and growth.